Travel to The City of Jakarta Using Public Transportation - Swantari, Anita; Festivalia, Filma; Wicaksono, Haryo; Hendradewi, Savitri; Haryono, Joko (Institut Pariwisata Trisakti, 2023)
This research aims to find out which tourists use public transportation provided by the DKI Jakarta Government. Public transportation is used to avoid traffic jams to get to tourist destinations comfortably and quickly. This research is qualitative research. The objects of this research are all public transportation places in the city of Jakarta and the seven tourist destinations most visited by tourists in Jakarta. The research was conducted by interviews and observations with the DKI Jakarta Transportation and Transportation Department and domestic and foreign tourists who use public transportation. The research results show that traveling to Jakarta using public transportation is a practical, efficient and often economical choice. Jakarta has various types of public transportation, including KRL, MRT, LRT, TransJakarta, Jaklingko, and online motorbike taxis, which can make it easier for tourists to explore various tourist attractions in this city. Jakarta has high safety standards in the field of public transportation, and passengers are expected to comply with applicable regulations and etiquette. Keywords: Public Transportation, Tourist Destinations